High-throughput screen for sorting cells capable of producing the biofuel feedstock botryococcene. Issue 12 (6th March 2019) - Chacko, Allen R.; Amster, Daniel E.; Johnson, Tyler E.; Newman, Sara R.; Gladchuk, Angelina V.; Sohn, Christine J.; Prunkard, Donna E.; Yakelis, Neal A.; Freeman, Jon O.
Abstract : Botryococcene is a branched triterpene produced by the algae Botryococcus braunii . Abstract : Botryococcene is a branched triterpene produced by the algae Botryococcus braunii . Hydrocracking botryococcene yields a variety of combustible fuels such as gasoline and jet fuel. Engineering host systems and proteins involved in the biosynthesis of botryococcene to optimize production is of interest given these applications. The current study investigates the use of a diaryltetrazole based screen that undergoes a photoclick reaction with terminal alkenes, such as the branched terminal alkene present on botryococcene, to yield a fluorescent product. Host E. coli systems were established to produce botryococcene, squalene, and no triterpene to serve as a control. Cells were incubated with tetrazole and briefly irradiated with UV light to initiate the photoclick reaction. It was found that the botryococcene producing cells yielded observable fluorescence while the squalene and control cells had negligible fluorescence turn-on activity. Fluorescence-activated cell sorting (FACS) was subsequently used to identify and sort botryococcene producing E. coli from a mixture of control and squalene producing cells.